2011
DOI: 10.1007/s00726-011-0983-2
|View full text |Cite
|
Sign up to set email alerts
|

Leucine nutrition in animals and humans: mTOR signaling and beyond

Abstract: Macronutrients, such as protein or amino acid, not only supply calories but some components may also play as signaling molecules to affect feeding behavior, energy balance, and fuel efficiency. Leucine, a branched-chain amino acid is a good example. After structural roles are satisfied, the ability of leucine to function as signal and oxidative substrate is based on a sufficient intracellular concentration. Therefore, leucine level must be sufficiently high to play the signaling and metabolic roles. Leucine is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(156 citation statements)
references
References 87 publications
4
144
2
6
Order By: Relevance
“…Dietary Leu suppresses skeletal muscle protein degradation (11,12,27), and enhances protein synthesis through activation of mTOR signaling (9,10,26). However, the effects of other amino acids on protein degradation and protein synthesis in skeletal muscle have scarcely been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary Leu suppresses skeletal muscle protein degradation (11,12,27), and enhances protein synthesis through activation of mTOR signaling (9,10,26). However, the effects of other amino acids on protein degradation and protein synthesis in skeletal muscle have scarcely been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that a single oral administration of Lys suppresses degradation of skeletal muscle protein, but may not enhance protein synthesis through the mTOR signaling although we did not measure the fractional synthesis rate. Dietary Leu stimulates protein synthesis by activating mTOR signaling (10,26,(34)(35)(36). Therefore, the regulation of protein turnover by Lys may be different from that of Leu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in ADG from 102% to 110% SID Leu : Lys resulted mainly from an increase in feed efficiency. Leucine is not only a substrate for protein synthesis but also acts as a signal stimulating protein synthesis and inhibiting protein degradation in skeletal muscle (Tischler et al, 1982;Escobar et al, 2005;Li et al, 2011). Experimental data reporting the effect of supplementing Leu on ADG in piglets are limited.…”
Section: Gloaguen Le Floc'h Primot Corrent and Van Milgenmentioning
confidence: 99%
“…Furthermore, these AA, along with glycine, tryptophan, tyrosine and D-amino acids (e.g., D-alanine, D-aspartate, and D-serine), regulate neurological development and function (Fernstrom 2012;Friedman and Levin 2012;Hou et al 2012a, b;Wang et al 2013). Moreover, leucine activates the mammalian target of rapamycin to stimulate protein synthesis and inhibit intracellular proteolysis (Dillon 2012;Li et al 2011b), whereas methionine is the major donor of the methyl group to affect DNA and protein methylation in cells (Wang et al 2012). Notably, nutritional studies have shown that dietary supplementation with several AA (e.g., arginine, glutamine, glutamate, leucine, and proline) modulates gene expression and enhances growth of the small intestine and skeletal muscle (Geng et al 2011;Jobgen et al 2009;Wang et al 2008;Wu et al 2011a, b; Regulation of acid-base balance (e.g., renal ammoniagenesis from glutamine)…”
Section: Introductionmentioning
confidence: 99%